Tratamento de efluentes contendo ibuprofeno utilizando membranas funcionalizadas - Spaciari, Ana Carolina (2022)
With the increasing development and population growth, the contamination rate of drinking water matrices with emerging contaminants containing pharmaceuticals, such as ibuprofen, has risen. These emerging pollutants have been generating concerns related to public health, fauna and flora, since they are cumulative and highly toxic. In order to develop an alternative and efficient method to remove drugs, the present work proposes the study and development of functionalized polymeric membranes to be used in filtration processes. Initially, the adsorption capacities of three different materials (graphene oxide, zeolite Y and MOF HKUST-1) were studied, varying the pH and temperature parameters and evaluating the influence on the kinetics and isotherms. Among them, MOF HKUST-1 presented ibuprofen removal higher than 90% (qmax 95,76±0,11 mg g-1). In the sequence, polymeric membranes functionalized with this composite were produced by the phase inversion method. The membranes produced presented high percentages of ibuprofen retention (>93%), and it was also possible to recover the permeate flux after filtration (>90%). The PVP copolymer conferred characteristics of higher porosity to the membranes and the HKUST-1 MOF provided a possible change in the polymeric structure, which also influenced the permeate flux and increased ibuprofen retention. When evaluating the different compositions, varying the amount of PVP and MOF HKUST-1 in the polymeric solution, through the flow and retention characteristics, it was possible to determine two membranes with higher retentions the M6F2 and the M7F2. These were finally evaluated with different filtration parameters (pressures of 0.50, 1.25 and 2 bar and feed concentrations of 10, 30 and 50 ppm), determining that the membrane with the best process conditions was the M7F2, with a maximum retention of 98.79%±0.24 at a pressure of 1.25 bar and feed of 50 ppm. The results suggest that the PES/PVP/HKUST-1 functionalized membrane has a great potential to be applied in the treatment of effluents containing ibuprofen.